Handling Patient Scheduling And Appointment Management: Best Practices For Medical Secretaries (Journal of Namibian Studies : History Politics Culture, 2022)
This abstract discusses best practices for medical secretaries in handling patient scheduling and appointment management within healthcare facilities. Efficient appointment scheduling is crucial for optimizing patient flow and ensuring timely access to care. This paper outlines key strategies for medical secretaries, including the utilization of electronic health record (EHR) systems, standardized scheduling protocols, proactive patient communication, efficient resource allocation, flexibility and adaptability, and ensuring confidentiality and data security. By implementing these best practices, medical secretaries can enhance operational efficiency, improve patient satisfaction, and contribute to the overall effectiveness of healthcare delivery.